Georgia Architectural and Historic Properties Survey of 410 West St., Valdosta, Ga., December 1980 - Smith, Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 410 West St., Valdosta, Ga., December 1980. 1 story rectangular shiplap sided house with gabled roof. Shed porch held up by square posts. Double hung sash windows with 2/2 lights. Set on brick piers. Poor condition. Date of Construction: App. 1922-1930. Functional house in densely populated area settle by low income. Significant as part of a potential N.R. district.
Georgia Architectural and Historic Properties Survey of 410 West St., Valdosta, Ga., December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 80.6 MB (84,539,544 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)